The Contribution of Artists Who Lived and Worked in Central Asia to the Development of Uzbek Music - qizi, Solijonova Durdonaxon Maxmudjon (Research Parks Publishing LLC, 2023)
In this article, the contributions of the great figures who lived and created in Central Asia to the art of Uzbek music were highlighted in this article. We tried to thoroughly analyze and illuminate several works written by great figures.